A HOMILETICAL INTERPRETATION BY REYNOLDS OF THE NARRATIVES OF PROPHET IBRAHIM AND AYUB - Anshori, Muhammad Helmi (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This study will examine the verses of the story using the intertextuality approach is a necessity to see the extent to which the Qur'an communicates with its audience in an effort to produce the religious message it wants to convey. This study is a literature study, whose data source is through verses of the Qur'an and Bible that specifically discuss the story of Prophet Ibrahim and Job. Then the verses are analyzed using Reynolds' intertextuality approach, namely the concept of homiletics which is then described as a result of the connection between the two. The results of this study conclude that the intertextuality side in the narrative of the Qur'an and Bibel about the story of Prophet Ibrahim both allude to a figure who has debated Prophet Ibrahim. The figure questioned and doubted the power of God from Prophet Ibrahim. Whereas in the story of Prophet Job in the narration of the Qur'an and the Bible have editorials that look similar between the two. But in substance, between the two there are differences in the model of delivering the message.